DETERMINATION OF THE CONTENT LEVEL OF INNOVATIVE ACTIVITY IN THE PREPARATION OF FUTURE PRIMARY SCHOOL TEACHERS FOR THE PROFESSIONAL SPECIALTY - Баймухамбетова, Куралай; Ibyraimzhanov, Kalibek (Pedagogy and Psychology, 2023)
In this article the author investigates the approach to innovative activities in the organization of quality education in the preparation of future primary school teachers from the point of view of modern educational and methodological issues. As an actual research problem of the modern education system in the formation and development of innovative opportunities for a future teacher in professional activities, his own judgments and conclusions are presented. One of the stages of the study related to the determination of the content level of the innovative professional activity of future primary school teachers is devoted to the analysis of the results of the content level. The authors, guided by regulatory documents, sought to justify the need to adapt to innovative activities as a professional, including the knowledge, skills and modern competencies inherent in a teacher, in theory and methodological content of the training of modern teachers. The research methodology was chosen on the basis of systematization of the theoretical and methodological foundations of the problem of training future primary school teachers, analysis of the works of scientists prepared in a new format (PhD). As a result of the analysis, directions of training future specialists based on innovative activities of students are discussed. Also, in order to determine the content level of research work, the authors of the article developed and implemented the author’s questionnaire "What do you know about innovative professional activity" 123 students of the educational program 6B130100 - "Training of teachers of pedagogy and methods of primary education" took part in the article and the analysis of the results of the meaningful level of their understanding of the need for innovation in their future professions is presented. The results of the study are organized on the basis of empirical methods.